Effect of Steel Fibers on the Mechanical Strength of Concrete - Muhamet Ahmeti; Driton Kryeziu; Mentor Ramadani (Civil Engineering Journal, 2022)
The study is based on designing the mix design of the concrete for the class named MR_DK_E1: C30/37, one of the most widely used classes of normal concrete. To see the effect of the fibers on concrete, we will design three mixtures that in other components are similar to the first mixture "Normal Concrete",but as an additive, we will add 0.75%, 1.5%, and 2.0% of steel fiber (Romfracht SRL Company Profile) to the mass of concrete. Although some researchers have already detailed the favourable qualities of steel fiber reinforced concrete (SFRC), there is very little data regarding the design and performance of this type of concrete. To get to know something more in terms of the properties of steel fiber reinforced concrete, during the realization of this work we will perform some experimental tests based on European standards to understand closely how fibers affect the growth and improvement of properties of concrete with lime aggregate and local cement CEM II/BM (WL) 42.5N, applying different percentages of fibers to the volume of the concrete. For all mixtures, the necessary tests on the properties of wet concrete and hardened concrete will be performed, while the obtained results will be compared between the same kinds, where conclusions and recommendations will be drawn that can serve for further studies and use in engineering practice in our country. Three different mixtures of fibre content were applied. Experiments show that for all selected mixtures of fibre content, a more ductile behaviour and higher load levels in the post-cracking range were obtained. The study forms the basis for the selection of suitable fibre types and content for their most efficient combination with regular steel bar reinforcement. Also, special attention will be given to the use of SFRC for constructive elements. This experimental research concerning SFRC has been performed in the building materials laboratory near UBT, the Proing laboratory-Pristina, and GIM-Skopje (Kosovo). Doi: 10.28991/CEJ-2022-08-09-010 Full Text: PDF